PENERAPAN MODEL PEMBELAJARAN BLENDED LEARNING UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA - Ni Wayan Sekarmini (Universitas Pendidikan Ganesha, 2022)
This classroom action research aimed to (1) find out whether the application of the blended learning learning model could increase learning motivation, (2) find out how much the increasein mathematics learning achievement with the application of the blended learning learningmodel, and (3) find out students' opinions on the application of the blended learning model.learning. This research was conducted at SMP Negeri 2 Selemadeg Timur which involved 18 students of class IX B in the second semester of the academic year 2021/2022. This research was conducted in three cycles. Data on students' learning motivation was collected using aquestionnaire and student achievement was collected by means of a learning achievement test in the form of a description, while students' opinions on the applied learning were collected using a questionnaire Further more, the data that has been collected was analysed using descriptive methods. The results showed that (1) there was an increase in student motivation at SMP Negeri 2 Selemadeg Timur after the application of the blended learning model in cycles I, II, and III, (2)an increase in the average achievement in cycle II increased by 3.61 and in the third cycle in creased by 3.28. Absorption capacity increased by 3.61% from cycle I to cycle II and 3.28%from cycle II to cycle III. While the classical learning completeness increased by 5.56% in the second cycle and by 11.11% in the third cycle, and (3) students' opinions on the applied learning were very positive.